Management of multi-source information to identify the typology of the horizontal structures in historical masonry buildings: the case study of the Museum of Capodimonte in Naples (Italy) - A. Maione; L.U. Argiento; C. Casapulla; A. Prota (Fracture and Structural Integrity)
The evaluation of the seismic safety of ancient masonry buildings usually requires compounding the need of preservation of the historical values with the need of achieving a proper level of knowledge of the parameters influencing their structural behaviour. To this aim, non-destructive techniques of instrumental investigation have lately attracted increasing attention, although the provided data are frequently not exhaustive and require to be integrated with different sources of information, such as historical documents and hypotheses of critical interpretation. Therefore, the management of this multi-source information is a crucial aspect in defining a methodological approach to the structural evaluation of the cultural heritage. This paper describes an integrated approach developed in the framework of the Project on the seismic evaluation of the Museum of Capodimonte in Naples (Italy) with reference to the typological identification of the horizontal structures upon the first level of the building. The management of the data derived from the application of the infrared thermography, integrated with the information from the visual inspections, the architectural survey and the historic analysis, has allowed obtaining a complete characterization of the structures under study.